Investigation of pore geometry influence on fluid flow in heterogeneous porous media: A pore-scale study - Soltanmohammadi, Ramin; Iraji, Shohreh; Rodrigues de Almeida, Tales; Basso, Mateus; Ruidiaz Munoz, Eddy; Campane Vidal, Alexandre (Energy Geoscience, 2024)
Brazilian pre-salt reservoirs are renowned for their intricate pore networks and vuggy nature, posing significant challenges in modeling and simulating fluid flow within these carbonate reservoirs. Despite possessing excellent petrophysical properties, such as high porosity and permeability, these reservoirs typically exhibit a notably low recovery factor, sometimes falling below 10%. Previous research has indicated that various enhanced oil recovery (EOR) methods, such as water alternating gas (WAG), can substantially augment the recovery factor in pre-salt reservoirs, resulting in improvements of up to 20%. Nevertheless, the fluid flow mechanism within Brazilian carbonate reservoirs, characterized by complex pore geometry, remains unclear. Our study examines the behavior of fluid flow in a similar heterogeneous porous material, utilizing a plug sample obtained from a vugular segment of a Brazilian stromatolite outcrop, known to share analogies with certain pre-salt reservoirs. We conducted single-phase and multi-phase core flooding experiments, complemented by medical-CT scanning, to generate flow streamlines and evaluate the efficiency of water flooding. Subsequently, micro-CT scanning of the core sample was performed, and two cross-sections from horizontal and vertical plates were constructed. These cross-sections were then employed as geometries in a numerical simulator, enabling us to investigate the impact of pore geometry on fluid flow. Analysis of the pore-scale modeling and experimental data unveiled that the presence of dead-end pores and vugs results in a significant portion of the fluid remaining stagnant within these regions. Consequently, the injected fluid exhibits channeling-like behavior, leading to rapid breakthrough and low areal swept efficiency. Additionally, the numerical simulation results demonstrated that, irrespective of the size of the dead-end regions, the pressure variation within the dead-end vugs and pores is negligible. Despite the stromatolite's favorable petrophysical properties, including relatively high porosity and permeability, as well as the presence of interconnected large vugs, the recovery factor during water flooding remained low due to early breakthrough. These findings align with field data obtained from pre-salt reservoirs, providing an explanation for the observed low recovery factor during water flooding in such reservoirs.